The reasoning of the judicial ruling in administrative cases and its applications in the courts of the Kingdom of Saudi Arabia (An applied systematic study) - Al-Juma, Anas Ayed (Journal of Islamic Sciences, 2023)
This research aims to study a topic that enriches the Administrative Judiciary and build on it the most important thing in the administrative judgements, which is the legal and jurisprudential causation of the judgement in administrative cases and its applications in Saudi Arabian courts as from legal and sharia aspects. Among the research objectives is to concentrate on the legitimacy of the causation of administrative judgements. The preamble identified the causation of judgements as well as the administrative case, The first chapter discussed the administrative judiciary's pillars, as well as the nature and validity of administrative cases. The second chapter discussed the legality of causation, the benefits of causation, and the tactic of causation, The third chapter presented the administrative judge's judicial authority in causation, which clarified the furniture of non-causation and included an administrative court application for causation.One of the study's most important findings is that causation in administrative judgements is regarded as important "because it serves as a guarantee for the parties to the conflict," as it places the reasons that prompted the authority to impose a penalty on the employee in his hands.
Keywords: administrative judgements; administrative lawsuit; causation of judgements; Administrative Judiciary